Self-consumption hunting during the COVID-19 pandemic: The Matsigenkas communities case from Manu National Park - Farfan Flores, Johny (2023)
In this work, we hypothesize that the period of isolation, immobilization, and reverse migration that occurred during the COVID-19 pandemic (years 2020 and 2021) increased the hunting capacity of the Matsigenka communities settled in Manu National Park (PN Manu). To evaluate this, we assessed changes in hunting volume patterns through participatory monitoring using the hunting intensity monitoring model. It was evident that there was an increase in the hunting capacity of Matsigenka communities. The highest extraction volumes and the greatest increase in the number of hunters, hunting effort, and hunting area occurred in the 2020-2021 period, the year in which isolation and immobilization measures were established. However, there was a decrease in the indicators for the 2021-2022 period, the year in which isolation measures were relaxed and economic reactivation occurred, allowing people to return to their economic and educational activities outside PN Manu. It should be considered that the effects of only one year of the pandemic on the livelihoods of the communities could have affected the abundance of wildlife, with vulnerable species such as maquisapa monkeys and choro monkeys experiencing high extraction rates. On the other hand, our results indicate that the good conservation status of PN Manu provided food provisions for the communities during the pandemic. Planning programs to mitigate the negative effects of pandemics or similar events is recommended, and the importance of measuring the resilience of key hunting species is emphasized, as increased hunting could also have effects on the food security of these communities.